2013
DOI: 10.1080/0305764x.2013.834036
|View full text |Cite
|
Sign up to set email alerts
|

Predicting pre-service teachers’ preparedness for inclusive education: Bangladeshi pre-service teachers’ attitudes and perceived teaching-efficacy for inclusive education

Abstract: This study reports on the second phase of a larger study, which investigated the preparedness of pre-service teachers to teach in inclusive classrooms in Bangladesh. Phase 1 employed two standardised scales that were used with 1623 pre-service teachers from 16 teacher education institutions to measure their attitudes and perceived teaching-efficacy for inclusive education. The findings of Phase 1 indicated that the level and length of training, along with gender, influenced both teacher attitudes and teaching-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 50 publications
5
48
1
2
Order By: Relevance
“…Peebles and Mondaglio (2014) found that both the inclusion course and the field experience (working with and planning for individual and small groups of learners) produced significant gains in pre-service teachers' self-efficacy. Moreover, Ahsan et al (2013) proved that appropriate curriculum (course) content was more important for teacher preparedness than the length of the programme. However, mere attendance of an inclusive pre-service teacher education course does not guarantee the development of positive attitudes and beliefs about inclusive practices (Angelides, Stylianou, & Gibbs, 2006;Forlin, Cedillo, Romero-Contreras, Fletcher, & Hernández, 2010).…”
Section: Effect Of Demographic Variables On Tepidmentioning
confidence: 99%
See 2 more Smart Citations
“…Peebles and Mondaglio (2014) found that both the inclusion course and the field experience (working with and planning for individual and small groups of learners) produced significant gains in pre-service teachers' self-efficacy. Moreover, Ahsan et al (2013) proved that appropriate curriculum (course) content was more important for teacher preparedness than the length of the programme. However, mere attendance of an inclusive pre-service teacher education course does not guarantee the development of positive attitudes and beliefs about inclusive practices (Angelides, Stylianou, & Gibbs, 2006;Forlin, Cedillo, Romero-Contreras, Fletcher, & Hernández, 2010).…”
Section: Effect Of Demographic Variables On Tepidmentioning
confidence: 99%
“…The provision of adequate and sufficient initial and in‐service teacher training on inclusion impacts positively on the teacher's perceived preparedness to teach in inclusive environments, indicating greater perceived confidence and self‐efficacy in applying appropriate inclusive instructional classroom practices (Ahsan, Deppeler, & Sharma, ; Coady, Harper, & de Jong, ; Das, Gichuru, & Singh, ; Florian & Rouse, ; Hettiarachchi & Das, ; Kormos & Nijakowska, ). Low levels of perceived preparedness may trigger the development of negative beliefs about inclusion (e.g., Das, Kuyini, & Desai, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In many countries, all teachers are mandated to learn about teaching students with disabilities. International research findings (Forlin et al, ; Ahsan, Deppeler & Sharma, ; Kim, ; Shade & Stewart, ) show that despite various initiatives having been undertaken to reform teacher preparation for inclusive classrooms, regular school teachers continue to have a lower sense of efficacy and have on‐going concerns about including children with disabilities in regular classrooms. Specifically, it has been noticed (Avramidis et al, ; Forlin, ; Schmidt & Vrhovnik, ; Scruggs & Mastropieri, ) that teachers tend to show more negative attitudes towards including children with high support needs (that is, students who use Braille and sign language, who need individual attention).…”
Section: Introductionmentioning
confidence: 99%
“…Forlin, 2010;Loreman, 2010;Walton & Rusznyak, forthcoming). There is also a surfeit of studies drawn from course evaluations as researchers try to show the effects of courses on pre-service teachers' attitudes to inclusive classrooms and dispositions towards teaching learners with disabilities (Ahsan, Deppeler & Sharma, 2013;Lambe & Bones, 2008). Our previous research considers the potential of undertaking practicum sessions in special school contexts for supporting the pedagogic learning of pre-service teachers (Walton & Rusznyak, 2013).…”
Section: Teacher Education For Inclusive Educationmentioning
confidence: 99%